Effectiveness of rural households' coping strategies against aggregate shocks - Jin, Ling; Filipski, Mateusz J.; Chen, Kevin Z. (China Agricultural Economic Review, 2014)
While rural households in developing countries deploy a series of risk coping strategies to insulate against shocks, their effectiveness relies extraordinarily on the nature of the shocks. Using unique datasets collected before and after the 2008 Sichuan earthquake, this paper examines the performance of all the principal coping strategies employed by the affected rural households. We find that the seven directly surveyed coping strategies can be ranked according to the receipts financed by applying them as depleting savings, government aid, subsidized bank loans, informal credit, private transfer, selling assets, and saving money by letting children drop out of school.